PERAN PENGAWAS DALAM MENERAPKAN PENGENDALIAN INTERN PEMBERIAN KREDIT PADA GABUNGAN KOPERASI PEGAWAI REPUBLIK INDONESIA JAWA TIMUR - Revi Arfamaini (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2019)
Introduction: Implementation of internal control is one of theorganization's efforts must be made to improve the effectiveness of its operations. How to implement internal control is to implement an integrated framework published by COSO in 1992. Internal control not only on the organization, credit unions must implement internal control. This is because credit unions have an activity in the form of lending on credit to members. Lending on credit can lead to an unsuccessfuluncollectible receivables that have threats that can cause harm. Threatsinclude non-performing loans, human error and fraud. Internal controls will be run in accordance with the plan, if the controller cooperativesperform functions as an internal auditor to evaluate and provide recommendations on the implementation of internal controlimprovements that have been running on credit unions. Thus, the purpose of this study was to determine the role of the controller as afunction of the internal auditor in the application of internal control ofcredit on GKPRI JATIM.Methods: The method used is the method of participation observationto determine the application of internal control GKPRI JATIM. Furthermore, assessment of internal control so as to know GKPRI JATIMcontroller role as internal auditor function components based control framework published by COSO in 1992.Results: As a result, controllers should consider several things that madecooperative organizational structure, procedures and policies areimplemented cooperative lending, risk mapping and assessment of allcredit control activities undertaken management to be able to detectproblems that emerge early on.Conclusion and suggestion: Thus, internal control can be run effectively.